1980
DOI: 10.1001/archpedi.1980.02130230053016
|View full text |Cite
|
Sign up to set email alerts
|

Diets for Children and Adolescents That Meet the Dietary Goals

Abstract: \s=b\The parents of many elementary and secondary schoolchildren ask pediatricians for advice on how to feed diets that are in line with the US Dietary Goals or the Dietary Guidelines for Americans. This article outlines an approach for planning diets that fit these recommendations while also assuring that intakes approximate the recommended dietary allowances and the estimated safe and adequate intakes of nutrients provided by the Food and Nutrition Board, National Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…2, 23 Dwyer 24 suggested that the simplest recommendation for reducing children's total fat and saturated fat intake is to substitute skim milk for whole milk. Commercial fat-modified products such as salad dressing and cheese may further reduce fat intake; however, potential benefits of fat substitutes are speculative, 25 and research on the safety and efficacy of fat replacements in children's diets is needed.…”
mentioning
confidence: 99%
“…2, 23 Dwyer 24 suggested that the simplest recommendation for reducing children's total fat and saturated fat intake is to substitute skim milk for whole milk. Commercial fat-modified products such as salad dressing and cheese may further reduce fat intake; however, potential benefits of fat substitutes are speculative, 25 and research on the safety and efficacy of fat replacements in children's diets is needed.…”
mentioning
confidence: 99%
“…The composition of consumed fatty acids remained unchanged re gardless of the proportion of calories provided by fat, and the PUFA/SFA ratio correlated negatively with calories provided by fat, but correlation coefficients were not significant. The potential risk of nutritional déficiences or deleterious effects due to a reduction in con sumed fat can be avoided if the nutrient requirements are fulfilled by proper food se lection [14,24], However, not only fat but also other food items comprised in the milk group, meat or in their substitutes were less frequently consumed in those with a low fat intake as we reported elsewhere [18,19]. The role of eating habits including both food selec tion and nutritional density is of particular importance for a properlv balanced diet [25,26], Furthermore, it should be noted that the collected data were analysed at four different points of time only, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in timing of development for different individuals and for each sex contributes to the variable nutrient needs of adolescents of the same age. Nutrient needs correlate with biological maturity, rather than with chronological age (40). Sexual maturity ratings or other clinical indices for assessing biological age are useful in making nutritional recommendations (142).…”
Section: Effects Of Puberty On Nutrient Needs and Dietary Habitsmentioning
confidence: 99%